Maternal iodine status during lactation and infant weight and length in Henan Province, China - Jin Yang; Lin Zhu; Xiaofeng Li; Heming Zheng; Zhe Wang; Zongyu Hao; Yang Liu (BMC, 2017)
Abstract Background Infants are very sensitive to iodine deficiency. Breastfed infants are dependent on maternal iodine intake. The aim of this study was to evaluate the relationship between maternal iodine status during lactation and infant weight and length. Methods A cross-sectional survey was conducted to investigate maternal iodine status and infant anthropometric measures in Henan Province, China. Only exclusive breastfeeding mothers and their infants < 6 months of age (n = 747) were included in our final analysis. Urine samples were collected from all the mothers and infants. Infant weight and length were measured and converted into weight-for-age Z-score (WAZ) and height-for-age Z-score (HAZ) using the World Health Organization (WHO) AnthroPlus software. Results The median urinary iodine concentration (UIC) in lactating women was significant lower than that in their infants (177.4 vs 261.1 μg/L, P < 0.001). A positive correlation was found between maternal and infant urinary iodine concentration (r = 0.203, P < 0.01). The mean HAZ and WAZ values were lowest in the infants whose mothers had UIC below 50 μg/L (n = 41). Infant WAZ with maternal UIC below 50 μg/L was significantly lower than those with maternal UIC of 50 μg/L or above (P = 0.043). After adjusting for confounding factors, there were significant differences in infant WAZ between maternal UIC groups. Conclusions The present study suggests that maternal iodine status during lactation may be related to their infant anthropometric index. Appropriate iodine intake of lactating women is beneficial for their infants.